Promoting health literacy through the teach back method among Iranian health ambassadors: A randomized controlled trial - Sotoudeh, Ahmad; Ardakani, Mojtaba Fattahi; Jadgal, Mohammad Saeed; Asadian, Ali; Zareipour, Morad Ali (Investigación y Educación en Enfermería, 2023)
Objective. Describe the effect the teach back method on promoting the health literacy of health ambassadors in Urmia County in 2020. Methods. In the present quasi-experiment, 200 persons over 14 years old participated. They were divided into two research groups, a control (n=100) and an intervention (n=100). The sampling method was simple randomization and the data collection instrument was a questionnaire comprised of demographic information and health literacy (HELIA). The educational intervention took 4 sessions each 45 minutes in length following the teach back method. The questionnaire-based data were collected once before the intervention and once again three months after the intervention. Results. The present findings showed that 54% of the control group and 50% of the intervention group had a good or very good level of health literacy before the intervention(p>0.05). However, after the intervention, 52% of the control and 78% of the intervention group had a good or very good level of health literacy. The present findings revealed that the mean scores of health literacy dimensions (access to information, reading, understanding, appraisal, decision-making) and the overall health literacy score were significantly higher in the intervention group than the control (after the intervention). Wilcoxon’s test results showed that the mean difference of the overall health literacy scores and the dimensions before and after the intervention were statistically significant (p<0.001). Conclusion. In the light of the present findings, we can conclude that participatory methods and the teach back method can improve health literacy, acquire reliable information and adopt healthy behaviors.